The Efficacy of eHealth Interventions for the Treatment of Adults Diagnosed With Full or Subthreshold Binge Eating Disorder: Systematic Review and Meta-analysis - Elnaz Moghimi; Caroline Davis; Michael Rotondi (JMIR Publications, 2021)
BackgroundThere has been a recent rise in the use of eHealth treatments for a variety of psychological disorders, including eating disorders. ObjectiveThis meta-analysis of randomized controlled trials is the first to evaluate the efficacy of eHealth interventions specifically for the treatment of binge eating disorder (characterized by compulsive overconsumption of food, in a relatively short period, and without compensatory behaviors such as purging or fasting). MethodsA search on the electronic databases PubMed, Web of Science, Embase, MEDLINE, and CINAHL was conducted for randomized controlled trials that compared the efficacy of eHealth treatment interventions with waitlist controls. ResultsFrom the databases searched, 3 studies (298 participants in total) met the inclusion criteria. All interventions were forms of internet-based guided cognitive behavioral therapy. The results of the analysis demonstrated that when compared with waitlist controls, individuals enrolled in eHealth interventions experienced a reduction in objective binge episodes (standardized mean difference [SMD] −0.77, 95% CI −1.38 to −0.16) and eating disorder psychopathology (SMD −0.71, 95% CI −1.20 to −0.22), which included shape (SMD −0.61, 95% CI −1.01 to −0.22) and weight concerns (SMD −0.91, 95% CI −1.33 to −0.48). There was no significant difference in BMI between the eHealth interventions and controls (SMD −0.01, 95% CI −0.40 to 0.39). ConclusionsThese findings provide promising results for the use of internet-based cognitive behavioral therapy for binge eating disorder treatment and support the need for future research to explore the efficacy of these eHealth interventions.